Kadar Protein Total Serum Tikus Putih yang Diinduksi Protein Sintetik Pengkode Protein Spike SARS-Cov-2 Isolat Indonesia dan Pemanfaatannya sebagai Poster - Eggan Supriyanto (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The novel coronavirus, SARS-CoV-2, is the causative agent of the global outbreak of coronavirus disease 2019 (COVID-19), which has been designated a pandemic by the World Health Organization (WHO). The current treatment and prevention of COVID-19 is the use of the antiviral drug remdesivir, and recovery plasma transfusion represents a potential therapeutic option for severe COVID-19 patients. However, the clinical benefit of remdesivir in patients with severe disease is limited. The spike protein plays a role in the entry of SARS-CoV-2 into human cells, and thus represents an effective vaccine target to prevent SARS-CoV-2 infection. Recombinant proteins have been produced, but further testing is required to assess their efficacy against the body's immune system. The objective of this study is to ascertain the efficacy of recombinant protein-based vaccines or therapeutics and to identify any potential adverse effects, which are crucial in the development of more effective immunization and therapeutic strategies. The study utilized white rats (Rattus norvegicus) of the Wistar strain. Immunization was achieved through the administration of a synthetic protein encoding the spike protein of SARS-CoV-2, the Indonesian isolate, on three separate occasions. Blood sampling was conducted from the orbital sinus. Serum collection was stored at 80°C. The experiment employed the Bradford method to quantify serum protein levels. The results of the independent t-test, a parametric statistical test, in the treatment group and the control group demonstrated that the p-value was 0.922 (p=0.922 > p=0.05), indicating that there was no statistically significant difference between the two groups. The statistical analysis of the protein injection treatment group with and without the addition of adjuvant demonstrated a significance value of 0.803 (p=0.803 > p=0.05), indicating that there is no significant difference to changes in its serum protein levels. The administration of recombinant protein does not result in alterations to serum protein levels. Consequently, the development of vaccines and therapies based on recombinant SARS-CoV-2 spike protein is a highly viable proposition.
Reupload Repository Mei 2026 :: Finalisasi Repositori File 19 Mei 2026_Kurnadi
Keywords: SARS-CoV-2; Recombinant Protein; Serum; Bradford